PENGARUH KREATIVITAS DAN MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR BAHASA ARAB DI MA DDI AL-BADAR - Muhammad Idris Usman (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
This article is the result of the research which discuss about: 1). The influence of creativity toward students’ Arabic achievement, 2). The influence of learning mo-tivation toward students’ Arabic achievement, 3. The influence of creativity and learning motivation toward students’ Arabic achievement at MA Al-Badar DDI Parepare. This research used quantitative approach with correlational design. The population of the research was all the students at MA Al-Badar DDI Parepare which consist of 112 with 55 samples. The instrument of research was question-naire. Data were analysed by descriptive statistics and inferential statistic. The re-sult of the research shows that 1) creativity has pocitive influence toward stu-dents’ learning achievement in Arabic language; 2) motivation has positive influ-ence toward leaning achievement at arabic language; 3) creativity together with motivation influence positively toward students achievement in Arabic language at MA Al-Badar DDI Parepare.